2021
DOI: 10.1080/19490976.2021.1930874
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio vulgaris, a potent acetic acid-producing bacterium, attenuates nonalcoholic fatty liver disease in mice

Abstract: The emerging evidence supports the use of prebiotics like herb-derived polysaccharides for treating nonalcoholic fatty liver disease (NAFLD) by modulating gut microbiome. The present study was initiated on the microbiota-dependent anti-NAFLD effect of Astragalus polysaccharides (APS) extracted from Astragalus mongholicus Bunge in high-fat diet (HFD)-fed mice. However, the exact mechanisms underlying the beneficial effects of APS on NAFLD formation remain poorly understood.Co-housing experiment was used to asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 79 publications
2
96
0
Order By: Relevance
“…We showed that in the group receiving GOS supplementation increasing Bifidobacterium abundance was related to reduced carbohydrate intake and increasing Desulfovibrio to increased carbohydrate intake. Desulfovibrio bacteria are generally associated with clinical intestinal disease [58], although certain species have been found to beneficial in non-alcoholic fatty acid liver disease [59]. The compositional abundances of Desulfovibrio in these data are low, and occurrence in the GOS group were greater than in the placebo group.…”
Section: Discussionmentioning
confidence: 74%
“…We showed that in the group receiving GOS supplementation increasing Bifidobacterium abundance was related to reduced carbohydrate intake and increasing Desulfovibrio to increased carbohydrate intake. Desulfovibrio bacteria are generally associated with clinical intestinal disease [58], although certain species have been found to beneficial in non-alcoholic fatty acid liver disease [59]. The compositional abundances of Desulfovibrio in these data are low, and occurrence in the GOS group were greater than in the placebo group.…”
Section: Discussionmentioning
confidence: 74%
“…Polysaccharides are usually found in plants and can regulate the gut microbiota in different conditions, thereby playing a key role in many chronic diseases [ 32 , 33 ]. Astragalus mongholicus polysaccharides were shown to alleviate nonalcoholic fatty liver disease through gut microbiota regulation in mice [ 34 ]. Phellinus linteus polysaccharide extracts could improve insulin resistance, ameliorate intestinal dysbiosis, and help maintain intestinal barrier function in a diabetic rat model by regulating gut microbiota composition [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As functional validation, we also detected a decreased level of H 2 S and the LBP in the HJZ group [ 53 ]. Interestingly, a recent study has found that an acetic acid-producing bacteria Desulfovibrio vulgaris from Desulfovibrionaceae also showed anti-NAFLD effects [ 54 ], which highlight that we should emphasize on function evaluation instead of structural description of gut microbiota. Furthermore, we also found JZG could increase the abundance of beneficial bacteria such as S24_7 and Lachnospiraceae.…”
Section: Discussionmentioning
confidence: 99%